Chemiluminescent self-reported unfolding of single-chain nanoparticles. Issue 42 (28th April 2021) - Bloesser, Fabian R.; Walden, Sarah L.; Irshadeen, Ishrath M.; Chambers, Lewis C.; Barner-Kowollik, Christopher
Abstract : We demonstrate the light-induced, crosslinker mediated collapse of linear polymer chains into single-chain nanoparticles (SCNPs) capable of self-reporting their unfolding. Abstract : We demonstrate the light-induced, crosslinker mediated collapse of linear polymer chains into single-chain nanoparticles (SCNPs) capable of self-reporting their unfolding. The crosslinker entails a phenyloxalate motif allowing for the targeted degradation of the SCNPs via addition of hydrogen peroxide that triggers chemiluminescence (CL). The time-dependant CL emission can serve as a guide to follow the time dependent unfolding of the SCNPs, allowing for a qualitative assessment of the underlying mechanism.